(untitled) (Global Journal of Science Frontier Research, 2025)
The dynamics of fluctuations in the intensity of galactic cosmic rays CR are studied at different phases of the solar cycle In the previously introduced parameter of CR fluctuations on rotation No 2597 January 2024 a precursor https www forshock ru predlong html of the beginning of the maximum of the new 25th cycle was registered Taking into account the lead time of the medium-term forecast 2 1 of the solar rotations the beginning of the maximum of the 25th cycle was expected for February-March 2024 The indicator marker of the beginning of the maximum of the new 25th cycle is a significantly low - diagnostic value of the CR fluctuation parameter on rotation No 2599 in March 2024 which was confirmed by the results of operative monitoring The question of further development of the new 25th cycle remains relevant CR data https cosmicrays oulu fi indicate a sharp and deep 20 decrease in CR intensity at the end of the 24th cycle comparable to cycle 21 in the early 80s 1982 Most likely the 11-year cyclicity of the Sun is restored possibly at a level above average Obviously this indicates a LOCAL nature of the failure in cycles 23-24 The previously established conservatism or invariance of the binary relationship amplitude-duration of the 11-year cycle is violated in the two previous cycles 23 and 24 The maximum area energy content or luminosity - solar constant occurs in cycle 23 with a subsequent significant decrease in energy content - luminosity of cycle 24 Nevertheless the INVARIANT with the characteristic scale of the duration of the physical 22-year cycle is preserved In this case after a local failure of the 11-year cyclicity in the 23-24 cycles the 11-year cyclicity in the new 25 cycle should be restored It is important to note that the Lorenz system according to G V Kuklin et al is capable of describing various stages of the system s evolution from the emergence of convection - the appearance of self-oscillations 11-year cyclicity when the critical temperature value is exceeded to the disappearance of self-oscillations entering to the chaotic regime of the strange attractor when the temperature decreases As it happened during the Maunder minimum essentially - a parametric phase catastrophe There are obviously - extremal cases There is also an intermediate situation or ARRHYTHMIA in the cyclic activity of the Sun a local failure when the invariant of the 22-year cycle is preserved modern cycles 23-24 and 19-20 and a global failure when the invariant of the 22-year cycle is violated Dalton minimum and Gleissberg minimum At the same time both the emergence and violation of cyclicity are organically linked by a common approach to the cyclic activity of the Sun as a mechanism for regulating energy In this in our opinion lies the nature of solar cyclicity 11-year and 22-year solar cyclicity is nothing other than a self-oscillating mechanism of release - regulation of energy in the convective zone of the Sun stabilizing its temperature